METODE DESAIN VDI 2221 UNTUK MERANCANGSKID MPFM SINGLE LINE - S.T., M.T., Rudi Kurniawan Arief, (Rang Teknik Journal, 2018)
MPFM (Multi Phase Flow Meter) is an on field tools to measure the flow and compotition of crude oil during mud logging process. This tool unit operated beside logging well area so the result can be obtained directly on site. Because of remote access in mining location, a small and lighter measuring unit tools required in order to have easy transportation, storaging and installing of the unit. The MPFM Single line unit then developed to answer this problems VDI 2221 design methode is using to design this new unit where the primary data gathered from litercy study, interview with the company’s management staffs and operators. This design methode obtain 4 product variations where 1st Varian was choosed as the best design.  Keywords: MPFM, VDI 2221, Design Methode, Mechanical Design.